Sustainable Fruit Preservation Using Algae-Based Bioactive Coatings on Textile Packaging - Zoha Shabbir; Kashif Javed; Imran Ahmad Khan; Asfandyar Khan; Muhammad Junaid Saleem (Resources)
This study explores the potential of using natural textile packaging infused with algae-based coatings as an eco-friendly alternative to traditional plastic packaging for extending fruit shelf life. Traditional plastic packaging is known to release harmful chemicals into both food and the environment, which underscores the need for safer, more sustainable alternatives. This study investigates algae from three distinct groups—green, red, and brown algae—renowned for their rich bioactive compounds that exhibit natural preservative properties. Algae powders were prepared via immersion in purified water, boiling, and mixing with gum arabic to form a gelatinous coating solution. The algae coating was applied to knitted fabric, which was then crafted into bags for storing fruits such as tomatoes and apples. Over 21 days, the texture, weight loss, and juice content of the fruits stored in algae-coated bags were monitored and compared to those stored in uncoated packaging. The results showed that fruits in algae-coated packaging demonstrated significantly less weight loss and retained better texture. In terms of weight, the combination of red, green, and brown algae-coated packaging demonstrated the lowest reduction in weight for tomatoes (4.2%) and apples (3.8%) after 21 days, outperforming uncoated packaging, which exhibited reductions of 11.2% and 10.8%, respectively. These findings support the potential of algae-coated textile packaging to reduce reliance on conventional plastics while maintaining fruit quality during storage.